Non-traumatic Low Back Pain: Five Case Reports and Al Wakra Recommendations - Elrobaa, Islam Hussam; Aldulimi, Hani Hamad; Khalid, Muayad Kasim; Dafalla, Elfadel Hamad; Khan, Abdulhadi Haider; Fathi, Bassam Adel; Mgaram, Mohamed Abu Elgasem; Elhag, Helmy Gouda; Ali, Nashat Nabil; His (Archives of Clinical and Medical Case Reports, 2020)
Low back pain (LBP) is the fifth most common reason for visiting a physician [1, 2]. Although non-traumatic LBP is benign, and self-limited in most cases, it occasionally indicates a serious disease. Emergency physician must able to distinguish between patients with benign non-traumatic LBP requiring merely history taking and physical examination and identify those with LBP indicative of a serious illness. In this article, we have discussed five such cases and have proposed some clinical recommendations to manage nontraumatic LBP to avoid missing the loss of diagnosis of a serious disease. <gdiv></gdiv>